PENGARUH INJEKSI PGF2α DENGAN HORMON PMSG PADA JUMLAH KORPUS LUTEUM, EMBRIO DAN JUMLAH ANAK KELINCI - Eko Marhaeniyanto; I Gedhe Putu Kasthama (Universitas Tribhuwana Tunggadewi, 2007)
This research that was aimed to elucidate the effects of injection PGF2α with hormone PMSG on amount of corpus luteum, embryo and litter size of rabbit, was conducted at Field Laboratory of Animal Husbandry Tribhuwana Tunggadewi University and Biomol Laboratory, Brawijaya University, Malang. A randomized block design was used in the study with 4 treatments which reviewed in 4 blocks. The treatments of PGF2α injection were: T0 = control, no injection of PGF2α, T1 = dose 0,1 ml or 0,5 mg in intramuscular injection of PGF2α; T2 = dose 02 ml or 1,0 mg in intramuscular injection of PGF2α and T3 = dose 0,3 ml or 1,5 mg in intramuscular injection of PGF2α. The results of this research showed that effects injection of PGF2α with hormone PMSG on amount of corpus luteum, embryo and litter size of rabbit were very significant (P